Plugging a Bipyridinium Axle into Multichromophoric Calix[6]arene Wheels Bearing Naphthyl Units at Different Rims. Issue 1 (9th January 2017) - Orlandini, Guido; Ragazzon, Giulio; Zanichelli, Valeria; Degli Esposti, Lorenzo; Baroncini, Massimo; Silvi, Serena; Venturi, Margherita; Credi, Alberto; Secchi, Andrea; Arduini, Arturo
Abstract: Tris‐( N ‐phenylureido)‐calix[6]arene derivatives are heteroditopic non‐symmetric molecular hosts that can form pseudorotaxane complexes with 4, 4′‐bipyridinium‐type guests. Owing to the unique structural features and recognition properties of the calix[6]arene wheel, these systems are of interest for the design and synthesis of novel molecular devices and machines. We envisaged that the incorporation of photoactive units in the calixarene skeleton could lead to the development of systems the working modes of which can be governed and monitored by means of light‐activated processes. Here, we report on the synthesis, structural characterization, and spectroscopic, photophysical, and electrochemical investigation of two calix[6]arene wheels decorated with three naphthyl groups anchored to either the upper or lower rim of the phenylureido calixarene platform. We found that the naphthyl units interact mutually and with the calixarene skeleton in a different fashion in the two compounds, which thus exhibit a markedly distinct photophysical behavior. For both hosts, the inclusion of a 4, 4 ′ ‐bipyridinium guest activates energy‐ and/or electron‐transfer processes that lead to non‐trivial luminescence changes. Abstract : Reinventing the wheel : The incorporation of photoactive units in the ureido‐calix[6]arene skeleton, combined with the ability of the latter to form pseudorotaxanes with bipyridinium guests, can lead to working devices driven by light‐activated processes. The synthesis and peculiar photophysical behavior of calix[6]arene wheels decorated with naphthyl moieties is presented, and the consequences of the inclusion of a dialkylbipyridinium guest into the calixarene cavity are described.